The study of mentoring and leader-member exchange (LMX) on organisational commitment among auditors in Malaysia - Leow, Kah Loong *; Khong, Kok Wei * (Sunway University College, 2009)
This study examines the relationship and the interaction of mentoring (psychosocial and career) with the four dimensions of LMX (affect, contribution, professional respect, and loyalty) on organisational commitment. Three hypotheses were tested in a study of auditors across Malaysia and who are registered with the Malaysian Institute of Accountants (MIA). Responses from individual auditors were analysed and participation was voluntary. The findings on direct effects reveal that predictor variables have a positive relationship with affective-normative commitment and only partially supported continuance commitment. The results find that the psychosocial aspects of Mentoring, Reciprocity and Contribution of LMX were positively related to the affective-normative commitment. Continuance commitment was significantly predicted by the contribution of LMX. The results partially supported the interaction effects of the affective-normative and continuance commitment. One implication is that Human Resource Departments should consider mentoring and LMX when encouraging employees to manifest high levels of organisational commitment.